Genetic Diversity of Multidrug-Resistant Pseudomonas aeruginosa Isolates Carrying bla VIM-2 and bla KPC-2 Genes That Spread on Different Genetic Environment in Colombia (2021)
ABSTRACT: Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen with an increase in the frequency of infections caused by multidrug resistant (MDR) and extensively drug resistant (XDR) strains, limiting the available therapeutic options. The most troublesome resistance is the acquisition and production of carbapenemases such as Verona integron-encoded metallo-b-lactamases (VIM), the most frequent and widespread, and the Klebsiella pneumoniae carbapenemases (KPC), which has continuously spread in the last decade. Its dissemination is linked to their location on mobile genetic elements (MGEs). In Colombia, VIM and KPC have been increasing in its frequency showing major successful dissemination. In this article, we molecularly characterized and analyzed the genetic context of blaVIM and blaKPC in carbapenem-resistant P. aeruginosa (CRPA) isolates from infected and colonized patients in two tertiary-care hospitals, one in Medellín and the other in a municipality close to Medellín, both areas with high carbapenemase endemicity in Colombia (2013–2015). Using whole-genome sequencing (WGS), we identified a remarkable variety of genetic backgrounds in these MDR P. aeruginosa isolates carrying blaKPC2 and blaVIM2. There were a diversity of class 1 integron and variations in the gene cassettes associated to blaVIM2, as well as a possible event of spread of blaKPC2 mediated by a plasmid that contained part of Tn4401b in one infection case. The dissemination of blaVIM2 and blaKPC2 in P. aeruginosa in this area in Colombia has been strongly influenced by successful international clones, carrying these genes and additional determinants of resistance on MGEs, accompanied by gene rearrangement under an antimicrobial selection pressure. These findings emphasize the need to implement control strategies based on rational antibiotic use.